Tính: 4^5.3^2+2^10-2^3.30
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(a,\left(-25\right).\left(75-45\right)-75.\left(45-25\right)\)
\(=\left(-25\right).20-75.20\)
\(=20.\left(-25-75\right)\)
\(=20.\left(-100\right)\)
\(=-2000\)
\(b,\frac{18.12-48.15}{-3.270-3.30}\)
\(=\frac{18.12-12.4.15}{-3.270-3.30}\)
\(=\frac{12.\left(18-60\right)}{-3.\left(270+30\right)}\)
\(=\frac{12.\left(-42\right)}{-3.300}\)
\(=\frac{14}{25}\)
\(c,\frac{2^5.7+2^5}{2^5.5^2-2^5.3}\)
\(=\frac{2^5.\left(7+1\right)}{2^5\left(25-3\right)}\)
\(=\frac{2^5.8}{2^5.22}\)
\(=\frac{8}{22}\)
\(=\frac{4}{11}\)
a: \(\dfrac{25\cdot9-25\cdot17}{-8\cdot80-8\cdot10}=\dfrac{25\cdot\left(-8\right)}{\left(-8\right)\cdot\left(80+10\right)}=\dfrac{25}{90}=\dfrac{5}{18}=\dfrac{250}{900}\)
\(\dfrac{48\cdot12-48\cdot15}{\left(-3\right)\cdot\left(270+30\right)}=\dfrac{48}{300}=\dfrac{8}{50}=\dfrac{144}{900}\)
\(\dfrac{2^5\cdot3}{600}=\dfrac{96}{600}=\dfrac{144}{900}\)
b: \(\dfrac{2^5\cdot7+25}{25\cdot5^2-2^5\cdot3}=\dfrac{32\cdot7+25}{25\cdot25-32\cdot3}=\dfrac{249}{529}=\dfrac{1743}{7\cdot529}\)
\(\dfrac{3^4\cdot5-3^6}{3^4\cdot13+3^4}=\dfrac{3^4\left(5-9\right)}{3^4\left(13+1\right)}=\dfrac{-4}{14}=\dfrac{-2}{7}=\dfrac{-1058}{7\cdot529}\)
a) \(\frac{25.9-25.17}{-8.80-8.10}=\frac{25.\left(9-17\right)}{-8.\left(80+10\right)}=\frac{25.\left(-8\right)}{-8.90}=\frac{5}{18}\)
b) \(\frac{48.12-48.15}{-3.270-3.30}=\frac{48.\left(12-15\right)}{-3.\left(270+30\right)}=\frac{48.\left(-3\right)}{-3.300}=\frac{4}{25}\)
c) \(\frac{2^5.7+2^5}{2^5.5^2-2^5.3}=\frac{2^5.\left(7+1\right)}{2^5.\left(5^2-3\right)}=\frac{2^5.8}{2^5.\left(25-3\right)}=\frac{2^5.8}{2^5.22}=\frac{4}{11}\)
d) \(\frac{3^4.5-3^6}{3^4.13+3^4}=\frac{3^4.\left(5-3^2\right)}{3^4.\left(13+1\right)}=\frac{3^4.\left(5-9\right)}{3^4.14}=\frac{3^4.\left(-4\right)}{3^4.14}=\frac{-2}{7}\)
Lời giải:
Gọi biểu thức là $A$
\(A=\frac{2^{10}.3^8+5.(2^2)^5.3^8}{2^{10}.(3^3)^3-2^{10}.(3^2)^4}=\frac{2^{10}.3^8+5.2^{10}.3^8}{2^{10}.3^9-2^{10}.3^{8}}\)
\(=\frac{2^{10}.3^8(1+5)}{2^{10}.3^8(3-1)}=\frac{6}{2}=3\)
1; 5.22 + (\(x\) + 3) = 52
5.4 + (\(x\) + 3) = 25
20 + (\(x\) + 3) = 25
\(x\) + 3 = 25 - 20
\(x+3\) = 5
\(x\) = 5 - 3
\(x\) = 2
Vậy \(x=2\)
2; 23 + (\(x\) - 32) = 53 - 43
8 + (\(x\) - 9) = 125 - 64
8 + (\(x\) - 9) = 61
\(x\) - 9 = 61 - 8
\(x\) - 9 = 53
\(x\) = 53 + 9
\(x\) = 62
Vậy \(x\) = 62
B = \(\frac{\frac{1}{2^{10}}.5-\frac{1}{\left(2^2\right)^5}.3}{\frac{1}{2^{10}}.\frac{1}{3}-\frac{1}{2^{11}}}=\frac{\frac{1}{2^{10}}.\left(5-3\right)}{\frac{1}{2^{10}}.\left(\frac{1}{3}-\frac{1}{2}\right)}=\frac{2}{\left(-\frac{1}{6}\right)}=2:\left(-\frac{1}{6}\right)=-12\)
\(4^5.3^2+2^{10}-2^3.30\)
\(=\left(2^2\right)^5.3^2+2^{10}-2^3.2.15\)
\(=2^{10}.9+2^{10}-2^4.15\)
\(=2^4.\left[\left(2^6.9-2^6\right).15\right]\)
\(=2^4.\left[2^6.\left(9-1\right).15\right]\)
\(=2^4.\left[2^6.2^3.15\right]\)
\(=2^{13}.15\)
45.32 + 210 - 23.30
= 213.15
#